Fatigue In Children With Cancer Who Receive Chemotherapy - Sri Hendrawati; Fanny Adistie; Nenden Nur Asriyani Maryam (Journal of Nursing Care, 2021)
Fatigue in children with cancer is a physical, mental, and emotional experience characterized by reduced energy, decreased physical activity, and increased feelings of fatigue. So far, health workers have assumed that fatigue is a subjective feeling and is not life-threatening. If not handled properly, fatigue can reduce the quality of life. This study aimed to identify the level of fatigue in children with cancer. This research used a descriptive quantitative method. According to the inclusion criteria: 1) the respondents are children with cancer aged 6-18 years; 2) the children is undergoing treatment or medication, and 3) the general condition of the children is good. Technique sampling used consecutive sampling to get 74 children with cancer. The instruments used were the Childhood Fatigue Scale (CFS) to measure the level of fatigue in children and the Fatigue Scale-Adolescent (FSA) to measure the level of fatigue in adolescents. Data analysis using the mean value and frequency distribution. The results showed that based on the fatigue questionnaire of children with cancer who receive chemotherapy, most of them had a severe fatigue scale of 56 people (75.7%). Meanwhile, a small proportion of children had a mild fatigue scale of as many as 18 people (24.3%). In this study, all children with cancer experienced fatigue. It interrupts or limits their daily activities and significantly influences different aspects of personal life. Children can still felt fatigued even after chemotherapy is over. Nurses as health workers who have the most frequent contact with children must provide appropriate nursing interventions for cancer to minimize fatigue.